RIPK4 Suppresses the Invasion and Metastasis of Hepatocellular Carcinoma by Inhibiting the Phosphorylation of STAT3 - Li, Haoran; Luo, Dingan; Huttad, Lakshmi; Zhang, Mao; Wang, Youpeng; Feng, Juan; Ding, Yunfeng; Han, Bing (Frontiers in Molecular Biosciences, 2021)
Receptor interacting serine/threonine kinase 4 (RIPK4) is a member of the threonine/serine protein kinase family; it plays related functions in a variety of tumours, but its biological function has not been fully revealed. It has been reported that it is differentially expressed in hepatocellular carcinoma (HCC). Our research aimed to reveal the role of RIPK4 in the progression of HCC and to reveal the biological behaviour of RIPK4 in HCC. We analysed the differences in RIPK4 expression in HCC by using a publicly available data set. By using PCR, Western blotting and immunohistochemical staining methods, we detected the expression level of RIPK4 in HCC patient specimens and studied the relationship between the expression of RIPK4 and the clinicopathological features of HCC patients. The prognostic data were combined to analyse the relationship between RIPK4 and HCC patient survival and tumour recurrence. We found that the expression level of RIPK4 in nontumour tissues was significantly higher than that in tumour tissues, and the level of RIPK4 was significantly positively correlated with postoperative survival and recurrence in HCC patients. Further, our study found that RIPK4 inhibits the progression of HCC by influencing the invasion and metastasis of HCC and that overexpression of RIPK4 reduces the invasion and metastasis of HCC by inhibiting epithelial-mesenchymal transition (EMT) and the STAT3 pathway. In in vivo experiments, overexpression of RIPK4 stably inhibited HCC metastasis. To summarize, our research revealed the relationship between RIPK4 and the prognosis of patients with HCC. We discovered that RIPK4 affects the invasion and metastasis of HCC through the EMT and STAT3 pathways. Targeted inhibition of the RIPK4 gene and the STAT3 pathway may be potential therapeutic strategies for inhibiting the postoperative recurrence and metastasis of HCC.